Respostas enzimáticas na enxertia de tomateiro - Gomes, Rafaelle F.; Cruz, Flávio J. R. [UNESP]; Nunes, Renata C.; Castoldi, Renata; Santos, Durvalina M. M. [UNESP]; Braz, Leila T. [UNESP] (FapUNIFESP (SciELO), 2016)
To evaluate the compatibility of tomato plants grafted onto different rootstocks under greenhouse conditions,the activity of antioxidant enzymes,peroxidases (POXs),polyphenol oxidase (PPO) and superoxide dismutase (SOD) were determined. The first experimental step was to assess,at six and eleven days after grafting,the grafted seedlings and non-grafted ones with three combinations of grafting (Maxifort,Multifort and selfgraft) in three collecting regions in the stem: a) 2 cm above the grafting region; b) on the grafting region c) 2 cm below the grafting region,in addition to further treatment,consisting of ungrafted seedlings of ‘Alambra’. The experimental design was completely randomized in a factorial 3x3+1,with five replications. The second experimental step was transplanting the seedlings to the greenhouse,with the combinations of grafting ‘Maxifort’,‘Multifort’,selfgraft and ungrafted,considering the plots combinations of grafting and the subplots the four collection periods 30 60,90 and 120 days after transplanting. The experimental design was a randomized block in a split plot scheme,each experimental plot consisted of six plants,with six replications. The results of the first stage showed an increase in the activity of POXs and PPO during grafting fixation with rootstocks ‘Maxifort’,‘Multifort’ and also in the selfgraft. In the second stage,there was a higher increase in SOD and POXs activity for the rootstock ‘Multifort’ at 120 days after transplanting. The grafted and ungrafted plants showed no signs of incompatibility,and the increased enzyme activity attributed to the healing process and lignification of grafted seedlings,having kept this behavior over the cycle of growth and development of tomato plants.
Enzymatic responses on tomato grafting
Keywords: Compatibility; Peroxidase; Polyphenol oxidase; Solanum lycopersicum; Superoxide dismutase